Deteksi dan Identifikasi Spesies Meloidogyne pada Tanaman Wortel dari Dataran Tinggi Malino, Gowa, Sulawesi Selatan - Hishar Mirsam; Supramana Supramana; Gede Suastika (The Indonesian Phytopathological Society (Perhimpunan Fitopatologi Indonesia), 2015)
Meloidogyne spp. was reported as the cause of branched tuber disease on several carrot production areas in Java, Indonesia and may potentially cause yield loss. This research aimed to use morphological and molecular characters to detect and identify Meloidogyne species on carrot from Malino Highland, Sub-district of Tinggimoncong, District of Gowa, South Sulawesi. Morphological identification was done based on character of the female perineal pattern. Molecular identification was based on amplification of r-DNA by polymerase chain reaction technique using species specific primers (Fjav/Rjav for M. javanica, Far/Rar for M. arenaria, and Finc/Rinc for M. incognita) and multiplex primer (JMV1/JMVhapla/JMV2 for M. hapla, M. chitwoodi, and M. fallax).Two of Meloidogyne species, i.e. M. incognita and M. arenaria were detected associated with the incidence of carrot branched tuber. The specific primers amplified two DNA bands, i.e. ± 999 bp of M. incognita and ± 420 bp of M. arenaria, while multiplex primer was failed to amplify DNA bands. Nucleotide sequence analysis showed M. incognita isolate of Malino was closely related to M. incognita isolate from Bangka-Indonesia, China (isolate JS2), and Malaysia (isolates JIK4, FIK4, JIT19, and FIT19) with homology of 99.2–100.0%. The nucleotide sequences of M. arenaria from Malino was submitted to GenBank with accession number KP234264, which was the first nucleotide sequence data in GenBank.